Method for degrading water-based polyacrylic acid emulsion by electrochemical oxidation method
By modifying the graphite sheet electrode and optimized electrolyte components, combined with ferric nitrate impregnation and carbonization treatment, the problems of low degradation efficiency and short electrode life in the prior art are solved, and efficient, economical and environmentally friendly degradation effects are achieved.
Patent Information
- Application Number
- CN202411953230.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The prior art has low degradation efficiency, short electrode life, high energy consumption, and secondary pollution and environmental protection problems when treating aqueous polyacrylic emulsions.
By carefully designing the electrode material preparation process, using modified graphite sheet electrodes and specific electrolyte components, combined with ferric nitrate impregnation and carbonization treatment, the electrolytic cell structure and reaction conditions are optimized to achieve efficient electrochemical oxidation and degradation.
It significantly improves the degradation rate of polyacrylic acid, improves current efficiency, reduces energy consumption, and reduces secondary pollution, providing an economical, efficient and environmentally friendly treatment solution.
Smart Images

Figure BDA0005215324460000121 
Figure BDA0005215324460000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polypropylene pollutant treatment, and in particular to a method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation. Background Art
[0002] When treating aqueous polyacrylic acid emulsions, traditional treatment methods such as physical adsorption are simple to operate, but can only adsorb polyacrylic acid on the surface of the adsorbent and fail to achieve its degradation. Subsequent treatment of saturated adsorbents will also cause secondary pollution and high costs. The chemical precipitation method has limited removal efficiency for polyacrylic acid because its mechanism of action is relatively simple and it is difficult to completely decompose polyacrylic acid molecules. In addition, the use of precipitants may introduce new impurity ions into the water body. The biodegradation method is greatly affected by environmental factors such as temperature, pH value, and microbial species and activity. Under unsuitable conditions, the degradation efficiency will be significantly reduced. In addition, the microbial culture and domestication process is complex and time-consuming, making it difficult to quickly respond to the treatment needs of large quantities of aqueous polyacrylic acid emulsions. In addition, some conventional electrochemical degradation methods often have problems such as short electrode life and low catalytic activity due to improper selection of electrode materials, resulting in low current efficiency and excessive energy consumption during the degradation process. At the same time, the electrolyte formula is not optimized enough to effectively maintain the stability of the reaction system and promote the degradation reaction of polyacrylic acid. In addition, the design of the electrolytic cell lacks specificity and the mass transfer efficiency between electrodes is poor, making it difficult for the degradation reaction to proceed fully and the overall degradation effect is unsatisfactory. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation in view of the deficiencies in the above-mentioned prior art. The present invention improves the catalytic activity and stability of the electrode and prolongs the service life of the electrode by carefully designing the electrode material preparation process, adopting a specific graphite film treatment method and combining the steps of ferric nitrate impregnation. The electrolyte composition and pH value are accurately adjusted to enhance the stability of the reaction system and promote the degradation reaction of polyacrylic acid. The electrolytic cell structure and parameters are reasonably designed, the electrode spacing, stirring device, etc. are optimized, and the mass transfer efficiency between electrodes is improved, so as to achieve efficient degradation of aqueous polyacrylic acid emulsion under suitable current density and temperature conditions, improve the degradation rate of polyacrylic acid and improve the current efficiency, reduce energy consumption, reduce secondary pollution, and provide an economical, efficient and environmentally friendly solution for the treatment of aqueous polyacrylic acid emulsion.
[0004] To achieve the above object, the technical solution adopted by the present invention is: a method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation, comprising the following steps:
[0005] S1. Preparation of electrodes:
[0006] The graphite sheet was bonded with PTFE resin to prepare a graphite sheet electrode, and then the graphite sheet electrode was placed on Fe 3+ The modified graphite sheet electrode is immersed in the solution, taken out after the immersion is completed, and carbonized under heating to obtain a modified graphite sheet electrode as an anode electrode; another graphite sheet electrode is directly heated and carbonized to obtain a cathode electrode;
[0007] S2, adding the polyacrylic acid emulsion to be treated into the electrolyte, and adding sodium sulfate;
[0008] S3, using a two-electrode system, the modified graphite sheet electrode prepared in step S1 is used as a cathode, and inserted into the electrolyte of step S2 for electrochemical oxidation treatment to degrade the polyacrylic acid emulsion in the electrolyte.
[0009] Preferably, the Fe in step S1 3+ The solution is ferric nitrate solution.
[0010] Preferably, the concentration of the ferric nitrate solution is 10-40 g / L.
[0011] Preferably, step S1 specifically comprises:
[0012] S1-1, crushing the graphite film into graphite sheets with a sheet diameter of 1-50 μm, and then bonding them with PTFE resin to form a graphite sheet electrode;
[0013] S1-2. Immerse the graphite sheet electrode in a 10-40 g / L ferric nitrate solution for 6-24 h, take it out and put it into a carbonization furnace for treatment at 450-550 ° C for 2.5-10 h, cool it to room temperature, and obtain a modified graphite sheet electrode as an anode electrode; take another graphite sheet electrode and directly heat it for carbonization to obtain a cathode electrode.
[0014] Preferably, step S1 specifically comprises:
[0015] S1-1, crushing a 25 μm thick graphite film into graphite sheets with a sheet diameter of 1-50 μm, and then bonding them with PTFE resin to form a graphite sheet electrode;
[0016] S1-2. Immerse the graphite sheet electrode in a 30 g / L ferric nitrate solution for 12 h, take it out and put it into a carbonization furnace for treatment at 500°C for 5 h, cool it to room temperature, and obtain a modified graphite sheet electrode as an anode electrode; take another graphite sheet electrode and directly heat it for carbonization to obtain a cathode electrode.
[0017] Preferably, step S2 specifically comprises:
[0018] The pH value of the electrolyte is adjusted to 6-8, and then the polyacrylic acid emulsion to be treated is added to control the concentration of polyacrylic acid in the electrolyte to be 5-20 g / L, and then sodium sulfate is added to a concentration of 10-30 g / L, and mixed evenly.
[0019] Preferably, in step S2, sodium hydroxide is used to adjust the pH value of the electrolyte.
[0020] Preferably, step S2 specifically comprises:
[0021] The pH value of the electrolyte was adjusted to 8 with sodium hydroxide, and then the polyacrylic acid emulsion to be treated was added to control the concentration of polyacrylic acid in the electrolyte to be 10 g / L, and then sodium sulfate was added to a concentration of 20 g / L, and mixed evenly.
[0022] Preferably, step S3 specifically comprises:
[0023] The anode electrode and the cathode electrode prepared in step S1 are combined into a two-electrode system, and inserted into the electrolyte of step S2 for electrochemical oxidation treatment to degrade the polyacrylic acid emulsion in the electrolyte;
[0024] The treatment process is kept stirring and the current density is 10-50mA / cm 2 , the processing temperature is controlled at 25-40℃.
[0025] Preferably, step S3 specifically comprises:
[0026] The anode electrode and the cathode electrode prepared in step S1 are combined into a two-electrode system, and inserted into the electrolyte of step S2 for electrochemical oxidation treatment to degrade the polyacrylic acid emulsion in the electrolyte;
[0027] The distance between the anode electrode and the cathode electrode was kept at 5 cm, the stirring speed was kept at 100 r / min, and the current density was 15 mA / cm 2 , the processing temperature is controlled at 40℃ and the processing time is 3h.
[0028] The beneficial effects of the present invention are:
[0029] The present invention provides a method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation, which has at least the following advantages:
[0030] 1. High-efficiency degradation performance: The present invention uses a carefully designed electrode material preparation process, a specific graphite film processing method, a 25 μm thick graphite film is crushed into 1-50 μm graphite sheets and bonded with PTFE resin, and then an anode is obtained by impregnation with iron nitrate and carbonization treatment, as well as optimized electrolyte composition (such as determining the polyacrylic acid concentration to be 10 g / L, adding sodium sulfate to enhance conductivity) and precisely controlled electrochemical reaction parameters (such as appropriate current density, pH value and temperature), which significantly improves the degradation rate of polyacrylic acid. For example, in Example 6, the degradation rate can reach 92%, which is greatly improved compared to the low degradation efficiency of conventional treatment methods in the prior art, and can more effectively remove organic pollutants in aqueous polyacrylic acid emulsions and achieve efficient degradation.
[0031] 2. Good current efficiency: Reasonable allocation of various components in the electrolyte, such as adding sodium sulfate to enhance conductivity, and precise control of reaction conditions, including the improvement of electrode activity by the iron nitrate impregnation step in the preparation of electrode materials, and the current density (such as determining 10-50mA / cm 2 range and preferably 15mA / cm 2 ), temperature (25-40°C, preferably 40°C) and pH value (6-8) are precisely controlled to reduce unnecessary power loss and improve current efficiency. For example, the current efficiency in Example 11 can reach 68%. Compared with the low current efficiency caused by improper selection of electrode materials or unreasonable reaction conditions in the prior art, the present invention effectively reduces energy consumption and makes fuller use of electrical energy.
[0032] 3. Simple and environmentally friendly process: The whole process mainly revolves around the key steps of electrode material preparation, electrolyte adjustment, electrolytic cell design, electrochemical reaction and post-treatment, and the operation is relatively simple. In the reaction process, through the reasonable control of reaction conditions, the occurrence of side reactions is reduced, and problems such as the introduction of new impurity ions by traditional chemical precipitation methods or secondary pollution by adsorption methods are avoided. It meets environmental protection requirements and is conducive to large-scale application in the treatment of aqueous polyacrylic acid emulsions, reducing negative impacts on the environment and promoting sustainable development.
[0033] 4. Optimization of electrode performance: The special electrode material preparation method makes the electrode have higher catalytic activity and stability, and prolongs the service life of the electrode. For example, the anode treated with iron nitrate impregnation shows better performance in the reaction, reducing the need for frequent replacement of electrodes due to electrode loss, reducing operating costs, and improving the economy and stability of the entire process. This is an advantage that is difficult to achieve in the case of insufficient electrode performance in the existing technology. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0035] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0036] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0037] The present invention provides a method for degrading an aqueous polyacrylic acid emulsion by electrochemical oxidation, which is characterized by comprising the following steps:
[0038] S1. Preparation of electrodes:
[0039] The graphite sheet was bonded with PTFE resin to prepare a graphite sheet electrode, and then the graphite sheet electrode was placed on Fe 3+ The modified graphite sheet electrode is immersed in the solution, taken out after the immersion is completed, and carbonized under heating to obtain a modified graphite sheet electrode as an anode electrode; another graphite sheet electrode is directly heated and carbonized to obtain a cathode electrode;
[0040] S2, adding the polyacrylic acid emulsion to be treated into the electrolyte, and adding sodium sulfate;
[0041] S3, using a two-electrode system, the modified graphite sheet electrode prepared in step S1 is used as a cathode, and inserted into the electrolyte of step S2 for electrochemical oxidation treatment to degrade the polyacrylic acid emulsion in the electrolyte.
[0042] In a preferred embodiment, the Fe in step S1 3+ The solution is ferric nitrate solution.
[0043] In a preferred embodiment, the concentration of the ferric nitrate solution is 10-40 g / L.
[0044] In a preferred embodiment, step S1 is specifically as follows:
[0045] S1-1, crushing the graphite film into graphite sheets with a sheet diameter of 1-50 μm, and then bonding them with PTFE resin to form a graphite sheet electrode;
[0046] S1-2. Immerse the graphite sheet electrode in a 10-40 g / L ferric nitrate solution for 6-24 h, take it out and put it into a carbonization furnace for treatment at 450-550 ° C for 2.5-10 h, cool it to room temperature, and obtain a modified graphite sheet electrode as an anode electrode; take another graphite sheet electrode and directly heat it for carbonization to obtain a cathode electrode.
[0047] In a preferred embodiment, step S1 is specifically as follows:
[0048] S1-1, crushing a 25 μm thick graphite film into graphite sheets with a sheet diameter of 1-50 μm, and then bonding them with PTFE resin to form a graphite sheet electrode;
[0049] S1-2. Immerse the graphite sheet electrode in a 30 g / L ferric nitrate solution for 12 h, take it out and put it into a carbonization furnace for treatment at 500°C for 5 h, cool it to room temperature, and obtain a modified graphite sheet electrode as an anode electrode; take another graphite sheet electrode and directly heat it for carbonization to obtain a cathode electrode.
[0050] Among them, PTFE resin has good chemical stability and high temperature resistance, which can enhance the overall performance of the electrode and prevent it from being corroded during the reaction. The purpose of impregnation with ferric nitrate solution is to introduce iron elements on the surface of the graphite sheet. In the subsequent carbonization process, the iron element can play a catalytic role and improve the electrocatalytic activity of the electrode.
[0051] In a preferred embodiment, step S2 is specifically as follows:
[0052] The pH value of the electrolyte is adjusted to 6-8, and then the polyacrylic acid emulsion to be treated is added to control the concentration of polyacrylic acid in the electrolyte to be 5-20 g / L, and then sodium sulfate is added to a concentration of 10-30 g / L, and mixed evenly.
[0053] When the pH value of the electrolyte is within the range of 6-8, the chemical environment of the electrolyte is relatively stable, which is conducive to the degradation reaction of polyacrylic acid and can reduce the corrosion of the electrode.
[0054] The concentration of polyacrylic acid in the electrolyte is determined based on a comprehensive consideration of multiple factors such as reaction rate, degradation effect and cost. At this concentration, the entire reaction system can be more economical and efficient while ensuring the degradation effect.
[0055] The role of sodium sulfate is to enhance the conductivity of the electrolyte, reduce the resistance during the reaction process, thereby improving the current efficiency and promoting the degradation reaction of polyacrylic acid.
[0056] In a preferred embodiment, sodium hydroxide is used to adjust the pH value of the electrolyte in step S2.
[0057] In a preferred embodiment, step S2 is specifically as follows:
[0058] The pH value of the electrolyte was adjusted to 8 with sodium hydroxide, and then the polyacrylic acid emulsion to be treated was added to control the concentration of polyacrylic acid in the electrolyte to be 10 g / L, and then sodium sulfate was added to a concentration of 20 g / L, and mixed evenly.
[0059] In a preferred embodiment, step S3 is specifically as follows:
[0060] The anode electrode and the cathode electrode prepared in step S1 are combined into a two-electrode system, and inserted into the electrolyte of step S2 for electrochemical oxidation treatment to degrade the polyacrylic acid emulsion in the electrolyte;
[0061] The treatment process is kept stirring and the current density is 10-50mA / cm 2 , the processing temperature is controlled at 25-40℃.
[0062] In a preferred embodiment, step S3 is specifically as follows:
[0063] The anode electrode and the cathode electrode prepared in step S1 are combined into a two-electrode system, and inserted into the electrolyte of step S2 for electrochemical oxidation treatment to degrade the polyacrylic acid emulsion in the electrolyte;
[0064] The distance between the anode electrode and the cathode electrode was kept at 5 cm, the stirring speed was kept at 100 r / min, and the current density was 15 mA / cm 2 , the processing temperature is controlled at 40℃ and the processing time is 3h.
[0065] The distance between the anode and cathode is kept at 5 cm. This electrode spacing design can ensure sufficient electric field strength while facilitating the transfer of substances between electrodes, avoiding the risk of short circuits caused by too small a spacing or the problem of low mass transfer efficiency caused by too large a spacing.
[0066] The function of the stirring device is to mix the electrolyte evenly in the electrolytic cell, ensure that the reactants are fully in contact with the electrode surface, and increase the reaction rate and degradation effect. At the same time, a DC power supply is connected to provide electrical energy for the electrochemical reaction.
[0067] The current density is adjusted according to actual needs and is generally controlled at 10-50mA / cm 2 In this current density range, the reaction can be effectively carried out to avoid problems such as too slow reaction rate due to too low current density or increased side reactions and increased electrode loss due to too high current density. The preferred current density is 30 mA / cm 2 .
[0068] Adjusting the pH value to neutral or weakly alkaline (pH 6-8) is beneficial to improving the degradation rate of organic matter. In this pH range, the ionization state of polyacrylic acid molecules is more suitable, and it is easier to undergo oxidation reaction on the electrode surface and be degraded.
[0069] The reaction temperature is maintained between 25-40°C. Too high a temperature will accelerate the corrosion of the electrode material, affecting the service life of the electrode and the stability of the reaction; too low a temperature will reduce the reaction rate. The preferred reaction temperature is 30°C, at which a relatively ideal reaction rate can be obtained while ensuring the life of the electrode.
[0070] The present invention has at least the following improvements:
[0071] 1. Preparation of special electrode materials: 25μm thick graphite film is crushed into 1-50μm graphite sheets, bonded with PTFE resin, and then impregnated with iron nitrate at a specific concentration (such as 30g / L is preferred) and carbonized at 500℃ to prepare the anode. In this process, the control of the diameter range of graphite sheets provides a large specific surface area, the iron nitrate impregnation introduces catalytic active elements, and the carbonization treatment enhances the stability and conductivity of the electrode. Together, they improve the catalytic activity and service life of the electrode, overcoming the problems of low electrode catalytic activity and short service life in the prior art, which is one of the key factors to achieve efficient degradation and good current efficiency.
[0072] 2. Accurate electrolyte control: The polyacrylic acid concentration in the electrolyte is accurately set to 10g / L, the pH value is adjusted to 6-8 with sodium hydroxide, and sodium sulfate is added as an additive. The determination of the polyacrylic acid concentration balances the degradation effect and cost, the appropriate pH range ensures the reaction stability and degradation efficiency, and sodium sulfate enhances the conductivity. These factors synergistically optimize the chemical environment of the reaction system, promote the degradation reaction of polyacrylic acid, and solve the problem of low reaction efficiency caused by poor electrolyte formulation in the prior art.
[0073] 3. Optimized electrolytic cell design and reaction condition control: adopt a two-electrode system and keep the distance between the anode and cathode at 5 cm, equip with a stirring device with specific parameters (diameter 3 cm, speed 100 r / min), and reasonably control the current density (10-50 mA / cm 2 , preferably 15mA / cm 2 ) and reaction temperature (25-40°C, preferably 40°C). The electrode spacing and stirring device parameters ensure the efficiency of material transfer between electrodes, and the appropriate current density and temperature range avoid the problems of increased side reactions, increased electrode loss, and too low reaction rate, so that the entire electrochemical reaction can be carried out efficiently and stably, effectively improving the unsatisfactory degradation effect caused by the lack of pertinence in electrolytic cell design and improper control of reaction conditions in the prior art.
[0074] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0075] Example 1
[0076] A method for degrading an aqueous polyacrylic acid emulsion by electrochemical oxidation, comprising the following steps:
[0077] S1. Preparation of electrode materials:
[0078] S1-1, a 25 μm thick graphite film (SDKFTR25, Jiangsu Stdick) was crushed into 1-50 μm graphite sheets using a crusher (Changzhou Hongshi Drying Technology, FS-124), and then bonded with PTFE resin by conventional technology to form a 10 mm (diameter) * 10 cm (length) graphite sheet electrode;
[0079] Quality Ratio:
[0080] The mass ratio of graphite sheet to PTFE resin is 7:3. This ratio ensures that the electrode has both sufficient conductivity and good mechanical strength and corrosion resistance.
[0081] Bonding process:
[0082] A 25 μm thick graphite film (model SDKFTR25, supplier Jiangsu Stdick) was crushed into graphite flakes with a diameter of 1-50 μm using a crusher (model FS-124, supplier Changzhou Hongshi Drying Technology).
[0083] The crushed graphite flakes and PTFE resin powder are mixed uniformly according to the above mass ratio.
[0084] Add an appropriate amount of deionized water to the mixture as a wetting agent to help the mixture adhere better.
[0085] The mixed materials were placed in a mold and pressed under a certain pressure to form a cylindrical structure with a diameter of 10 mm and a length of 10 cm.
[0086] The pressed sample is placed in an oven and dried at a temperature of about 100°C for several hours to remove excess moisture or solvent and ensure that the PTFE resin is fully cured to obtain a graphite sheet electrode.
[0087] S1-2, immerse the graphite sheet electrode in a 20g / L iron nitrate (Chinese medicine, purity 99%) solution for 12h, take it out and put it into a carbonization furnace for treatment at 500℃ for 5h, cool it to room temperature, and obtain a modified graphite sheet electrode as an anode electrode; take another graphite sheet electrode and directly put it into a carbonization furnace for treatment at 500℃ for 5h (i.e., not immersed in the iron nitrate solution), cool it to room temperature, and obtain a cathode electrode;
[0088] Anode Electrode:
[0089] The graphite sheet electrode prepared in S1-1 was immersed in a 20 g / L ferric nitrate solution (Sinopharm Group, purity 99%) for 12 hours to allow the ferric nitrate to be adsorbed on the surface of the graphite sheet.
[0090] After the impregnation was completed, the electrode was taken out and washed with deionized water, and then placed in a carbonization furnace, heated to 500°C at a heating rate of 5°C / min under nitrogen protection, and maintained at this temperature for 5 hours for heat treatment.
[0091] After the treatment is completed, the electrode is naturally cooled to room temperature to finally obtain a modified graphite sheet electrode as an anode electrode.
[0092] Cathode Electrode:
[0093] Another graphite sheet electrode that has not been impregnated with the ferric nitrate solution is directly placed in the carbonization furnace and heat treated under the same conditions (ie, 500° C. for 5 hours).
[0094] After cooling to room temperature, an unmodified graphite sheet electrode was obtained, which served as a cathode electrode.
[0095] S2. Electrolyte adjustment:
[0096] The pH value of the electrolyte was adjusted to 8 with sodium hydroxide (National Pharmaceutical Group, purity 99%), and then polyacrylic acid (SDK-08, produced by Jiangsu Stdick) was added to control the concentration of polyacrylic acid in the electrolyte to 10 g / L, and then sodium sulfate was added as an additive with a concentration of 20 g / L, and mixed evenly.
[0097] Main components of electrolyte:
[0098] The main component of the electrolyte is deionized water, which serves as a solvent to provide a reaction medium.
[0099] Specific composition:
[0100] Deionized water: As a solvent, it provides the liquid environment required for the electrochemical reaction.
[0101] Sodium hydroxide (NaOH): used to adjust the pH value of the electrolyte to 8. The product produced by Sinopharm Group with a purity of 99% is selected.
[0102] Polyacrylic acid (PAA): Model SDK-08, produced by Jiangsu Stdick, and its concentration in the electrolyte is controlled to be 10 g / L.
[0103] Sodium sulfate (Na2SO4): As a supporting electrolyte, it enhances the conductivity of the solution, helps stabilize the current density, and promotes electrochemical reactions. It is produced by Sinopharm Group and has a purity of 99%.
[0104] Sodium sulfate concentration point value:
[0105] The specific concentration of sodium sulfate is selected to be 20 g / L. This concentration can effectively improve the conductivity of the solution without causing excessive salt content, thereby avoiding corrosion to the equipment or increasing subsequent processing costs.
[0106] S3, electrolysis reaction:
[0107] The anode electrode and the cathode electrode prepared in step S1 are combined into a two-electrode system, and inserted into the electrolyte of step S2 for electrochemical oxidation treatment to degrade the polyacrylic acid emulsion in the electrolyte;
[0108] The distance between the anode and cathode was kept at 5 cm, the stirring speed was kept at 100 r / min (the diameter of the stirring device was 3 cm), and the current density was 10 mA / cm 2 , the processing temperature is controlled at 25℃.
[0109] Processing results:
[0110] After 3 hours of treatment, the degradation rate and current efficiency of polyacrylic acid were measured by HPLC. The results showed that the degradation rate of polyacrylic acid reached 65% and the current efficiency was 40%.
[0111] Example 2
[0112] Preparation of electrode materials: Similar to Example 1, except that the concentration of ferric nitrate is 30 g / L.
[0113] Electrolyte adjustment: same as in Example 1.
[0114] Electrolysis reaction: conditions are the same as in Example 1.
[0115] Treatment results: degradation rate 85%, current efficiency 60%.
[0116] Example 3
[0117] Preparation of electrode materials: The concentration of ferric nitrate is 50 g / L, and the rest is the same as in Example 1.
[0118] Electrolyte adjustment: same as in Example 1.
[0119] Electrolysis reaction: Same as Example 1.
[0120] Treatment results: degradation rate 75%, current efficiency 50%.
[0121] Example 4
[0122] Preparation of electrode materials: Similar to Example 2, except that the concentration of ferric nitrate is 30 g / L.
[0123] Electrolyte adjustment: same as in Example 1.
[0124] Electrolysis reaction: two-electrode system, electrode distance 5 cm, stirring device (diameter 3 cm, speed 100 r / min), current density 30 mA / cm 2 , reaction temperature 30℃.
[0125] Treatment results: HPLC showed that the degradation rate of polyacrylic acid was 85% and the current efficiency was 60%.
[0126] Example 5
[0127] Preparation of electrode materials: same as in Example 1.
[0128] Electrolyte adjustment: same as in Example 1.
[0129] Electrolysis reaction: The conditions were the same as in Example 1, except that the reaction temperature was raised to 35°C.
[0130] Treatment results: degradation rate 88%, current efficiency 62%.
[0131] Example 6
[0132] Preparation of electrode materials: same as in Example 1.
[0133] Electrolyte adjustment: same as in Example 1.
[0134] Electrolysis reaction: The conditions were the same as in Example 1, and the reaction temperature was 40°C.
[0135] Treatment results: degradation rate 92%, current efficiency 65%.
[0136] Example 7
[0137] Preparation of electrode materials: same as in Example 1.
[0138] Electrolyte adjustment: same as in Example 1.
[0139] Electrolysis reaction: The conditions are the same as those in Example 3, and the reaction temperature is 45°C.
[0140] Treatment results: degradation rate 89%, current efficiency 61%.
[0141] Example 8
[0142] Preparation of electrode materials: same as in Example 1.
[0143] Electrolyte adjustment: same as in Example 1.
[0144] Electrolysis reaction: The conditions were the same as in Example 1, and the reaction temperature was 50°C.
[0145] Treatment results: degradation rate 86%, current efficiency 58%.
[0146] By comparing Examples 4 to 8, it can be seen that, based on Example 2, when the reaction temperature is 40° C., the comprehensive performance of polyacrylic acid degradation rate and current efficiency is optimal.
[0147] Example 9
[0148] Preparation of electrode materials: same as in Example 6.
[0149] Electrolyte adjustment: same as Example 6.
[0150] Electrolysis reaction: two-electrode system, electrode distance 5 cm, stirring device (diameter 3 cm, speed 100 r / min), current density 5 mA / cm 2 , reaction temperature 40℃.
[0151] Treatment results: HPLC showed that the degradation rate of polyacrylic acid was 75% and the current efficiency was 45%.
[0152] Example 10
[0153] Preparation of electrode materials: same as in Example 6.
[0154] Electrolyte adjustment: same as Example 6.
[0155] Electrolysis reaction: conditions are the same as in Example 6, current density 10 mA / cm 2 .
[0156] Treatment results: degradation rate 80%, current efficiency 55%.
[0157] Embodiment 11
[0158] Preparation of electrode materials: same as in Example 6.
[0159] Electrolyte adjustment: same as Example 6.
[0160] Electrolysis reaction: conditions are the same as in Example 6, current density 15 mA / cm 2 .
[0161] Treatment results: degradation rate 90%, current efficiency 68%.
[0162] Example 12
[0163] Preparation of electrode materials: same as in Example 6.
[0164] Electrolyte adjustment: same as Example 6.
[0165] Electrolysis reaction: conditions are the same as in Example 6, current density 25 mA / cm 2 .
[0166] Treatment results: degradation rate 85%, current efficiency 58%.
[0167] By comparing Examples 9-12, it can be seen that based on Example 6, the current density is 15 mA / cm 2 When , the degradation rate and current efficiency of polyacrylic acid reached a better level.
[0168] In summary, through the study of multiple groups of examples, it is determined that the concentration of iron nitrate in the present invention is 30g / L, the reaction temperature is 40°C, and the current density is 15mA / cm 2 When the electrode material preparation, electrolyte adjustment, electrolytic cell design and electrochemical reaction and other aspects work together, the degradation rate and current efficiency of polyacrylic acid in the electrochemical oxidation degradation of aqueous polyacrylic acid emulsion can achieve relatively better results, which are significantly better than other parameter combinations, reflecting the effectiveness and advancement of the technical solution of the present invention.
[0169] The reaction conditions and treatment results of the embodiments are summarized in Table 1 below:
[0170] Table 1
[0171]
[0172]
[0173] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation, characterized in that: The following steps are involved: S1. Preparation of electrodes: The graphite sheet was bonded with PTFE resin to prepare a graphite sheet electrode, and then the graphite sheet electrode was placed on Fe 3+ The modified graphite sheet electrode is immersed in the solution, taken out after the immersion is completed, and carbonized under heating to obtain a modified graphite sheet electrode as an anode electrode; another graphite sheet electrode is directly heated and carbonized to obtain a cathode electrode; S2, adding the polyacrylic acid emulsion to be treated into the electrolyte, and adding sodium sulfate; S3. Using a two-electrode system, the modified graphite sheet electrode prepared in step S1 is used as a cathode and inserted into the electrolyte of step S2 for electrochemical oxidation treatment to degrade the polyacrylic acid emulsion in the electrolyte.
2. The method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation according to claim 1, characterized in that: Fe in step S1 3+ The solution is ferric nitrate solution.
3. The method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation according to claim 2, characterized in that: The concentration of the ferric nitrate solution is 10-40 g / L.
4. The method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation according to claim 1, characterized in that: Step S1 is specifically as follows: S1-1, crushing the graphite film into graphite sheets with a sheet diameter of 1-50 μm, and then bonding them with PTFE resin to form a graphite sheet electrode; S1-2. Immerse the graphite sheet electrode in a 10-40 g / L ferric nitrate solution for 6-24 h, take it out and put it into a carbonization furnace for treatment at 450-550 ° C for 2.5-10 h, cool it to room temperature, and obtain a modified graphite sheet electrode as an anode electrode; take another graphite sheet electrode and directly heat it for carbonization to obtain a cathode electrode.
5. The method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation according to claim 4, characterized in that: Step S1 is specifically as follows: S1-1, crushing a 25 μm thick graphite film into graphite sheets with a sheet diameter of 1-50 μm, and then bonding them with PTFE resin to form a graphite sheet electrode; S1-2. Immerse the graphite sheet electrode in a 30 g / L ferric nitrate solution for 12 h, take it out and put it into a carbonization furnace for treatment at 500°C for 5 h, cool it to room temperature, and obtain a modified graphite sheet electrode as an anode electrode; take another graphite sheet electrode and directly heat it for carbonization to obtain a cathode electrode.
6. The method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation according to claim 1, characterized in that: Step S2 is specifically as follows: The pH value of the electrolyte is adjusted to 6-8, and then the polyacrylic acid emulsion to be treated is added to control the concentration of polyacrylic acid in the electrolyte to be 5-20 g / L, and then sodium sulfate is added to a concentration of 10-30 g / L, and mixed evenly.
7. The method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation according to claim 6, characterized in that: In step S2, sodium hydroxide is used to adjust the pH value of the electrolyte.
8. The method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation according to claim 7, characterized in that: Step S2 is specifically as follows: The pH value of the electrolyte was adjusted to 8 with sodium hydroxide, and then the polyacrylic acid emulsion to be treated was added to control the concentration of polyacrylic acid in the electrolyte to be 10 g / L, and then sodium sulfate was added to a concentration of 20 g / L, and mixed evenly.
9. The method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation according to claim 1, characterized in that: Step S3 is specifically as follows: The anode electrode and the cathode electrode prepared in step S1 are combined into a two-electrode system, and inserted into the electrolyte of step S2 for electrochemical oxidation treatment to degrade the polyacrylic acid emulsion in the electrolyte; The treatment process is kept stirring and the current density is 10-50mA / cm 2 , the processing temperature is controlled at 25-40℃.
10. The method for degrading aqueous polyacrylic acid emulsion by electrochemical oxidation according to claim 9, characterized in that: Step S3 is specifically as follows: The anode electrode and the cathode electrode prepared in step S1 are combined into a two-electrode system, and inserted into the electrolyte of step S2 for electrochemical oxidation treatment to degrade the polyacrylic acid emulsion in the electrolyte; The distance between the anode electrode and the cathode electrode was kept at 5 cm, the stirring speed was kept at 100 r / min, and the current density was 15 mA / cm 2 , the processing temperature is controlled at 40℃ and the processing time is 3h.
Citation Information
Patent Citations
Cathode for lithium-containing batteries and solvent-free method for the production thereof
CN104170125A
Electrode applied to electrocatalytic degradation of organic pollutants as well as preparation method and application thereof
CN108862483A
Boron-doped diamond electrode sewage treatment experimental device and operation method thereof
CN111517420A
Binder complex single wall carbon nanotube and ptfe, electrode production composition using same, and secondary battery
CN116568639A
Preparation method of composite binder for dry-method electrode and electrode diaphragm
CN117384567A
Cited By
Methods and equipment for shortening preparation cycle and synergistic regulation of interfacial tension in pectin electrochemical modification and emulsification enhancement
CN122564570A